Organizational Capabilities of Retail Companies to Develop Green Marketing Strategies - Escalera Chávez, Milka Elena (2022)
The human being has damaged the planet by the indiscriminate consumption of products that are not friendly to the environment, hence now the trend of consumers to choose sustainable products. This is the reason why companies are changing the way they make their products, as well as the style of communication to inform that their products are favorable to the environment. The scope of this work is to assess retail enterprises ability for developing green marketing strategies. The study is quantitative-exploratory based on a non-probabilistic sample. A questionnaire was applied to 30 business owners and/or managers. Data was analyzed by using the principal components method. It was observed that the retail companies in Rioverde city, San Luis Potosí (S.L.P.) are able to develop green marketing strategies. The correlation matrix shows acceptable correlations and the values of the Sample Adequacy Measure (MSA) values are greater than 0.500: These values allow corroborating that the data structure is adequate to be examined by factor analysis. The analysis detects two latent factors that together explain 69.18% of the common variance. The results indicate that green marketing strategies require that owners or managers reformulate their business and processes from different perspectives: internally and with their customers. With respect the first point, staff must be trained on the importance of ecological products for the environment, health and the benefits for the company. With reference to, the second point, the owner or manager must identify the specific market for these products, because customers are varied and with different needs.